Biotransformation of menadione to its prenylated derivative MK-3 using recombinant Pichia pastoris. (1st July 2017) - Li, Zhemin; Zhao, Genhai; Liu, Hui; Guo, Yugang; Wu, Hefang; Sun, Xiaowen; Wu, Xihua; Zheng, Zhiming
Abstract: Prenylated quinones, especially menaquinones, have significant physiological activities, but are arduous to synthesize efficiently. Due to the relaxed aromatic substrate specificity and prenylation regiospecificity at the ortho- site of the phenolic hydroxyl group, the aromatic prenyltransferase NovQ from Streptomyces may be useful in menaquinone synthesis from menadione. In this study, NovQ was overexpressed in Pichia pastoris . After fermentation optimization, NovQ production increased by 1617%. Then the different effects of metal ions, detergents and pH on the activity of purified NovQ were investigated to optimize the prenylation reaction. Finally, purified NovQ and cells containing NovQ were used for menadione prenylation in vitro and in vivo, respectively. Menaquinone-1 (MK-1) was detected as the only product in vitro with γ, γ -dimethylallyl pyrophosphate and menadione hydroquinol substrates. MK-3 at a concentration of 90.53 mg/L was detected as the major product of whole cell catalysis with 3-methyl-2-buten-1-ol and menadione hydroquinol substrates. This study realized whole cell catalysis converting menadione to menaquinones.